Analisis Pengaruh Penggunaan Aplikasi ERP (Enterprise Resource Planning) Oracle E-Business Suite sebagai Penunjang Siklus Penjualan pada PT. Penta Valent Padang - Adam Dewandiva Maliki; Firman Surya; Muhammad Rafi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study aims to analyze the use of the Enterprise Resource Planning application Oracle E-Business Suite (ERP-EBS) as a support system for the sales cycle at PT Penta Valent Padang Branch. The research employs a descriptive qualitative method, with data collected through interviews and document reviews. The findings indicate that ERP-EBS has been comprehensively implemented across almost all business activities at the branch, covering customer order processing, inventory management, product delivery, as well as receivables, payment collection, and operational expense recording. Each department has clearly defined and integrated responsibilities, allowing business processes to run efficiently and be well-documented. In terms of benefits, the system enhances administrative efficiency, improves data accuracy, enables real-time transaction tracking, and strengthens internal control through interdepartmental data integration. However, the study also identifies challenges, such as the need for user adaptation due to system complexity and potential technical disruptions from the central server. Overall, the implementation of ERP-EBS has proven effective in improving the efficiency and effectiveness of the sales cycle at PT Penta Valent Padang Branch and supports positive user acceptance in line with the Technology Acceptance Model.